Fun stories about Brucella: the "furtive nasty bug". - Letesson, J-J; Lestrate, P; Delrue, R-M; Danese, I; Bellefontaine, F; David Fretin; Taminiau, B; Tibor, A; Dricot, A; Deschamps, C; Haine, V; Leonard, S; et al. (Vet Microbiol, 2002)
Although Brucella is responsible for one of the major worldwide zoonosis, our understanding of its pathogenesis remains in its infancy. In this paper, we summarize some of the research in progress in our laboratory that we think could contribute to a better understanding of the Brucella molecular virulence mechanisms and their regulation.
Keywords: Animals; Brucella; Brucellosis; Cell Communication; Cell Cycle; Flagella; Humans; Luminescent Measurements; Vibrio; Zoonoses